2005
DOI: 10.1081/ese-200056163
|View full text |Cite
|
Sign up to set email alerts
|

Root Responses and Metal Accumulation in Two Contrasting Ecotypes ofSedum AlfrediiHance Under Lead and Zinc Toxic Stress

Abstract: Sedum alfredii Hance has been reported to be a Zn-hyperaccumulator plant species. In this study, root morphological and physiological response of the hyperaccumulating ecotype of S. alfredii H. (HE) from the mined area and the non-hyperaccumulating ecotype of S. alfredii H. (NHE) from the agricultural area to supplied levels of Zn and Pb were investigated. The results showed that Zn concentrations in the leaves and the stems of the HE were 34 and 41 times higher, whereas lead concentrations were 1.9 and 2.4 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 22 publications
3
30
2
Order By: Relevance
“…The change in pH may be due to release of some root exudates in response to the stress to adapt itself with the existing environment. Wagner (1997) found that at water temperature of 25 o C, both A. pinnata and A. filiculoides showed maximum growth at pH values from 5-7. pH seems to be the most important parameter in the biosorptive process: it affects the solution chemistry of the metals, the activity of functional groups in biomass and competition of metallic ions (Li et al, 2005). Maximum turbidity was observed as 10.60 on the 12 th day at 75 ppm concentration and a minimum turbidity was observed as 0.75 on the 0 day in control set.…”
Section: Ph and Turbiditymentioning
confidence: 86%
See 2 more Smart Citations
“…The change in pH may be due to release of some root exudates in response to the stress to adapt itself with the existing environment. Wagner (1997) found that at water temperature of 25 o C, both A. pinnata and A. filiculoides showed maximum growth at pH values from 5-7. pH seems to be the most important parameter in the biosorptive process: it affects the solution chemistry of the metals, the activity of functional groups in biomass and competition of metallic ions (Li et al, 2005). Maximum turbidity was observed as 10.60 on the 12 th day at 75 ppm concentration and a minimum turbidity was observed as 0.75 on the 0 day in control set.…”
Section: Ph and Turbiditymentioning
confidence: 86%
“…'b' (Table 2). Chlorophyll content in plants correlates directly to the healthiness of plant (Li et al, 2005). Several cases of decreased chlorophyll content owing to metal toxicity have been reported in the plant kingdom growing in wetland ecosystems (Valavanidis et al, 2005).…”
Section: Photosynthetic Pigments Chlorophyllsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicates that the production of biomass is partially dependent of the root length, since higher root length promotes higher uptake of water and nutrients. Li et al (2005) reported that length, surface area and volume of roots of the hyperaccumulator ecotype of Sedum alfredii increased with high levels of Zn, whereas in the non-hyperaccumulator these parameters were significantly decreased. It has been reported that under Zn excess, the DNA synthesis and mitotic activity of root tips may be inhibited, which subsequently results in inhibition of root growth (Jain et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Several environmental factors influence root morphology, such as metal stress (Li et al, 2005) and nutrient availability (Zhang et al, 2003). The inhibition of root elongation is one of the major responses of plants to excess metals and may occur faster than other physiological responses.…”
Section: Resultsmentioning
confidence: 99%